Pengaruh Penerapan E-Filling Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Purnaningsih, Ni Komang Cahyani; Noviari, Naniek (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
The development of increasingly sophisticated technology now makes it easier for humans to do various jobs. The purpose of this study was to determine the level of individual taxpayer compliance that was influenced by the application of e-filling at KPP Pratama Gianyar. The method of data analysis uses path analysis. The research data uses primary data, namely the answers of individual taxpayers registered at KPP Pratama Gianyar for the questionnaire given. The results of this study indicate that business expectations and knowledge possessed by users have a positive influence on user compliance. Security and confidentiality of data, the speed of reporting has a positive influence on interest in using e-filling. Keywords : E-Filling,  compliance, knowledge, security, confidentiality.